2019
DOI: 10.1158/1078-0432.ccr-19-0365
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Glasdegib for Newly Diagnosed Acute Myeloid Leukemia

Abstract: On November 21, 2018, the FDA approved glasdegib (Daurismo; Pfizer), a small-molecule Hedgehog inhibitor, in combination with low-dose cytarabine (LDAC) for treatment of newly diagnosed acute myeloid leukemia (AML) in adults ! 75 years or with comorbidities that preclude use of intensive induction chemotherapy. Evidence of clinical benefit came from Study BRIGHT AML 1003, a randomized trial comparing glasdegibþLDAC with LDAC alone for treatment of newly diagnosed AML in 115 patients either ! 75 years old or ! … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 11 publications
0
65
0
1
Order By: Relevance
“…Three oral SMO antagonists, vismodegib (GDC-0449), sonidegib (LDE225), and glasdegib (PF-04449913), have been approved by the Food and Drug Administration (FDA) and show significant activity in locally advanced and metastatic basal cell carcinoma, as well as in AML. [599][600][601] Vismodegib was the first proposed Hh pathway inhibitor in cancer research 602 and is approved by the FDA 603 for local or advanced metastatic basal cell carcinoma treatment. 599 Subsequently, phase I and phase II trials targeting recurrent medulloblastoma have shown that the progression-free survival (PFS) of Shh-mb patients treated with vismodegib is longer and more effective than that of non-Shh-mb patients.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Three oral SMO antagonists, vismodegib (GDC-0449), sonidegib (LDE225), and glasdegib (PF-04449913), have been approved by the Food and Drug Administration (FDA) and show significant activity in locally advanced and metastatic basal cell carcinoma, as well as in AML. [599][600][601] Vismodegib was the first proposed Hh pathway inhibitor in cancer research 602 and is approved by the FDA 603 for local or advanced metastatic basal cell carcinoma treatment. 599 Subsequently, phase I and phase II trials targeting recurrent medulloblastoma have shown that the progression-free survival (PFS) of Shh-mb patients treated with vismodegib is longer and more effective than that of non-Shh-mb patients.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
“…Glasdegib was the first Hh pathway inhibitor approved for the treatment of AML in patients older than 75 years or those unable to use intensive induction chemotherapy 601 and showed good safety and tolerability in a phase I trial for patients with partial hematologic malignancies in Japan. 613 In a phase II trial, glasdegib combined with cytarabine/daunorubicin had a significant efficacy in patients with AML, chronic myeloid leukemia (CML) or high-risk myelodysplastic syndromes.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
“…Furthermore, several clinical trials investigating the use of SMO inhibitors alone or in combination with compounds blocking driver mechanisms in AML have been initiated. In fact, the SMO inhibitor Glasdegib, in combination with low-dose cytarabine, was recently approved for AML treatment of elderly patients [206].…”
Section: Type III Signaling-paracrine Shh Ligand-dependentmentioning
confidence: 99%
“…In the mammary system, inhibiting Hedgehog signaling reduces not only the ability of mammary CSCs to form primary spheres, but also their ability to self-renew and form secondary spheres (Liu et al, 2006b). Hedgehog signaling has been shown to be critical for the maintenance of stem cells in myeloid leukemia (Zhao et al, 2009); this and other observations formed the basis of trials testing Hedgehog antagonists in myeloid leukemia and ultimately led to the recent approval for Glasdegib in AML (Norsworthy et al, 2019). Since activated Hedgehog signaling can also up-regulate drug transporters on the surface of CSCs and thus promote chemoresistance (Sims-Mourtada et al, 2007), this pathway may regulate several aspects of the stem cell state and broadly promote cancer progression.…”
Section: Stem Cell Signals In Cancermentioning
confidence: 99%